"A real double-edged sword:" Undergraduate perceptions of social media in their learning. (December 2016) - Smith, Erika E.
Abstract: This study investigates undergraduate perceptions of the social media technologies (SMTs) they use in their learning. This mixed methods inquiry employed 30 semi-structured interviews and an online survey ( N = 679) to explore why and how undergraduates from across disciplines view SMTs to be a meaningful part of their university learning. Findings shed new insights into student perspectives on and uses of social media, and the variety of ways in which undergraduates intentionally choose (or, choose not) to incorporate social media into their university learning in meaningful ways. Student perceptions formed an overarching theme of social media as a double-edged sword that both informs and distracts, having the potential to both help and hinder learning. Together, the interviews and the open-ended survey results demonstrate that several contextual relationships exist, underscoring the importance of considering affordances of social media for learning. Rather than taking an approach founded upon technological determinism, learning context and social media affordances become key. Undergraduate perceptions of educational interactions via social media illustrate the prominence of student-student and student-content, rather than faculty-student, interactions via social media in their learning, allowing for an updated understanding of previous educational interactions models. Graphical abstract: Highlights: Social media is a "double-edged sword" that can both help and hinder learning. Student-student and student-content educational interactions are most prominent. Affordances and context for social media in higher education become key. Recommendations include developing digital literacies in undergraduate education.